2019
DOI: 10.1155/2019/3614207
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Gene Expression Prognostic Signature for Overall Survival in High-Grade Serous Ovarian Cancer

Abstract: The objective of this research was to develop a robust gene expression-based prognostic signature and scoring system for predicting overall survival (OS) of patients with high-grade serous ovarian cancer (HGSOC). Transcriptomic data of HGSOC patients were obtained from six independent studies in the NCBI GEO database. Genes significantly deregulated and associated with OS in HGSOCs were selected using GEO2R and Kaplan–Meier analysis with log-rank testing, respectively. Enrichment analysis for biological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In addition to the gastrointestinal cancers, we have also successfully established a 27-gene panel for lung adenocarcinoma (22), and a 11-gene panel for ovarian cancer (23). In such cases, we first demonstrated that these expression-based signatures were able to better predict prognosis in comparison with other already published multigene signatures using the same datasets, as described in detail below, which clearly indicate that our strategy has its own advantage.…”
Section: Prognostic/predictive Multigene Expression Signature Develop...mentioning
confidence: 60%
“…In addition to the gastrointestinal cancers, we have also successfully established a 27-gene panel for lung adenocarcinoma (22), and a 11-gene panel for ovarian cancer (23). In such cases, we first demonstrated that these expression-based signatures were able to better predict prognosis in comparison with other already published multigene signatures using the same datasets, as described in detail below, which clearly indicate that our strategy has its own advantage.…”
Section: Prognostic/predictive Multigene Expression Signature Develop...mentioning
confidence: 60%
“…Bioinformatics analyses have provided useful results based on large experimentally validated data accesible in various databases. Gene expression prognostic signature for high-grade serous ovarian cancer was investigated by resampling/cross-validation method with Cox regression analysis followed by Kaplan–Meier analysis and log-rank testing [ 62 ]. Similarly, He et al [ 63 ] probed the survival analysis of the expression level of MANF in HCC using the Kaplan–Meier method.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed a clinically applicable and robust prognostic signature for CRC patients using our multistep bioinformatics analysis strategy. [5][6][7][8] For our gene expression signature development, we first identified 738 genes (971 gene probe IDs) that were consistently deregulated in CRC versus normal colon tissue in six transcriptome datasets ( Figure 1A and B, Figure S1A, Table S1). Kaplan-Meier survival analysis together with Cox regression was used to evaluate whether their expression levels were associated with overall survival (OS) in GSE17536 dataset.…”
Section: Identification Of a Novel 15-gene Expression Signature Predimentioning
confidence: 99%
“…However, there is still an urgent need to develop better and more robust gene signatures in this area. In this study, we developed a clinically applicable and robust prognostic signature for CRC patients using our multistep bioinformatics analysis strategy 5–8 …”
Section: Figurementioning
confidence: 99%